Native arbuscular mycorrhizal fungi in the Yungas forests, Argentina - Becerra, Alejandra Gabriela (2011)
The arbuscular mycorrhizal fungal (AMF) communities from the Yungas forests of Argentina were studied. The AMF species present in the rhizosphere of some dominant native plants (one tree: Alnus acuminata; three herbaceous species: Duchesnea indica, Oxalis conorrhiza, Trifolium aff. repens; and one shrub: Sambucus peruviana) from two sites (Quebrada del Portugue´s and Narvaéz Range) of the Yungas forests were isolated, identified and quantified during the four seasons of the year. Twenty-two AMF morphotaxa were found. Spore density of some AMF species at each site varied among seasons. The genera that most contributed to the biodiversity index were Acaulospora for Quebrada del Portugue´s and Glomus for Narvaéz Range. High diversity values were observed in the Yungas forests, particularly in the spring (rainy season). We concluded AMF differed in species composition and seasonal sporulation dynamics in the Yungas forests.